Case report: Brachial plexopathy caused by malignant peripheral nerve sheath tumor and review of the literature - Chen, Mengjie; Li, Xiuli; Feng, Xinhong (Frontiers in Neurology, 2023)
Brachial plexopathy (BP) is easily misdiagnosed due to its complexity and varying clinical presentation. Malignant peripheral nerve sheath tumors (MPNST) can accumulate in the brachial plexus and share symptoms with BP, which may hinder the differential diagnosis between BP induced by radiation or metastases, and MPNST-derived BP, in patients with a history of breast cancer and radiation exposure. A 34-year-old Chinese female presented with MPNST. The tumor involved the brachial plexus. She had a history of breast cancer and radiotherapy. The first consideration was radiation- or breast cancer metastasis-derived BP. Clinical examination was performed. Finally, a diagnosis of MPNST of the brachial plexus was made, which guided an accurate treatment plan. This report highlights the importance of correctly diagnosing BP etiology for guiding precise treatment. BP caused by MPNST needs to be considered in clinical practice, and biopsy plays a central role in the differential diagnosis. Complete local surgical resection can prolong survival of patients with MPNST and improve treatment prognosis.